2009
DOI: 10.1507/endocrj.k08e-329
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of BRAFV600E in Altered Gene Expression in Papillary Thyroid Cancer

Abstract: Abstract. Somatic mutations in BRAF, especially BRAFV600E, are frequently identified in papillary thyroid cancer (PTC) tumors. It has been established that expression levels of numbers of genes are characteristically altered in PTC, however, the link between BRAF mutation and gene expression patterns are still elusive. In the present study, we analyzed relative expression levels of the wild type BRAF and BRAFV600E mRNA by using quantitative PCR (qPCR) and cDNA-PCR-RFLP in 19 PTC specimens and adjacent normal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…Vasko et al proposed an association between CDC42/PAK signaling and the mechanisms of PTC invasion. In opposition to their results, Watanabe et al (2009) performed a QPCR analysis to show a positive correlation between the BRAF V600E mutation and over-expression of vimentin, which was confirmed using NPA cells (inhibition of BRAF expression decreased vimentin levels). These authors also showed the BRAF V600E-dependent upregulation of fibronectin and CITED1, both of which have been identified as PTC markers.…”
Section: Transcriptome Of Papillary Thyroid Cancermentioning
confidence: 89%
“…Vasko et al proposed an association between CDC42/PAK signaling and the mechanisms of PTC invasion. In opposition to their results, Watanabe et al (2009) performed a QPCR analysis to show a positive correlation between the BRAF V600E mutation and over-expression of vimentin, which was confirmed using NPA cells (inhibition of BRAF expression decreased vimentin levels). These authors also showed the BRAF V600E-dependent upregulation of fibronectin and CITED1, both of which have been identified as PTC markers.…”
Section: Transcriptome Of Papillary Thyroid Cancermentioning
confidence: 89%
“…BRAF mutation is uniquely associated with the over-expression of many classical tumor-promoting molecules in PTC. Examples include VEGF,44 c-MET,41 matrix metalloproteinase,29,42,45,46 nuclear factor kappa B,46 Ki-67,27 prohibitin,47 and vimentin 48. Aberrant promoter methylation of several tumor suppressor and DNA repair genes in association with BRAF mutation was also demonstrated and associated with aggressive pathological characteristics of PTC 49,50.…”
Section: Braf Mutation and Aggressive Pathological And Molecular Deramentioning
confidence: 99%
“…Following the activation of the MAPK pathway, secondary molecular events occur, such as hypomethylation and genome-wide hypermethylation, which augment the tumorigenic activity of this pathway [52]. In addition, upregulation of several oncogenic proteins, such as chemokines [53,54], nuclear factor B (NF-B) [55], vascular endothelial growth factor A (VEGFA) [56], matrix metalloproteinases (MMPs) [53,55,57], MET [58,59], vimentin [60], prokineticin 1 (PROK1; also known as EG VEGF) [61], prohibitin [62], hypoxia-inducible factor 1␣ (HIF1␣) [63], thrombospondin 1 (TSP1) [64], urokinase plasminogen activator (uPA) and its receptor (uPAR) [65,66] and transforming growth factor ␤1 (TGF␤1) [67,68] drive cancer cell growth, proliferation and survival, together with tumor angiogenesis, invasion and metastasis.…”
Section: The Mapk Signaling Pathwaymentioning
confidence: 99%